CALCULATION OF HUMAN RESOURCES USING THE RESOURCE LEVELING FOR LABOR EFFICIENCY IN THE NEW MARKET DEVELOPMENT PROJECT OF MANDAILING NATAL REGENCY - Nessi Deva Fitriani; Mizanuddin Sitompul (Jurnal Media Teknik Sipil Samudra, 2021)
Manpower is one of the important human resources often limited availability, either due to quality factors or other reasons. In the construction phase, there is often a problem of unequal labor requirements that affect the allocation of labor. To minimize labor fluctuations using the resource leveling method. This study aims to determine the effect of resource leveling on the workforce on the allocation of labor on the construction under review and determine the allocation of human resources in implementation based on planning data. The object of this research is the construction of a new market in the Mandailing Natal district. The technique used in the resource leveling method research uses the help of the microsoft project program. This study shows that there is an influence of resources leveling on the workforce (workers, builders, head builders, foreman) on the allocation of labor in construction. The available workface are 50 workers, 32 carpenters, 22 carpenters, 2 head craftsmen, 1 foreman with a duration of work of 330 days. The leveling results show that with the available workforce, both with a fixed or unrestricted duration of work, there are some workers who are overallocated. From the results of the analysis, for a work duration of 330 days, the required number of workers includes 91 workers, 41 carpenters, 16 carpenters, 3 head craftsmen, 3 foreman.